2014
DOI: 10.1177/0011128714540277
|View full text |Cite
|
Sign up to set email alerts
|

Offense Type and the Arrest Decision in Cases of Intimate Partner Violence

Abstract: Although previous research has examined arrests for intimate partner violence (IPV), most of these analyses focus exclusively on physical assault and intimidation. Research on arrests for sexual assault have examined arrests for cases of stranger and/or acquaintance sexual assault, but have not included sexual IPV. Using data from the 2010 National Incident-Based Reporting System, this analysis is the first to calculate and compare arrest rates for sexual IPV, physical IPV, and intimidation. Results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 36 publications
(68 reference statements)
9
56
0
Order By: Relevance
“…Presently, jurisdictions have moved toward primary aggressor laws or proarrest laws (Messing et al, 2015). Despite these changes, the majority of IPV incidents do not result in arrest (Durfee & Fetzer, 2016; Eitle, 2005).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, jurisdictions have moved toward primary aggressor laws or proarrest laws (Messing et al, 2015). Despite these changes, the majority of IPV incidents do not result in arrest (Durfee & Fetzer, 2016; Eitle, 2005).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
“…The most robust and consistent predictors of arrest in IPV incidents included the presence of a weapon (Dichter et al, 2011; Durfee & Fetzer, 2016; Eigenberg et al, 1996; Eitle, 2005; Hamilton & Worthen, 2011), victim injury (Bachman & Coker, 1995; Buzawa & Austin, 1993; Dichter et al, 2011; Durfee & Fetzer, 2016; Eitle, 2005; Hamilton & Worthen, 2011; Robinson & Chandek, 2000; Tatum & Pence, 2015), presence of witnesses (Buzawa & Austin, 1993; Eigenberg et al, 1996; Hamilton & Worthen, 2011; Robinson & Chandek, 2000), and victim preference (Buzawa & Austin, 1993; Eigenberg et al, 1996). Extralegal factors, such as alcohol involvement, have also predicted arrest (Dichter et al, 2011; Durfee & Fetzer, 2016; Hamilton & Worthen, 2011; Roark, 2016). In terms of race/ethnicity, some studies have demonstrated that arrest has increased in IPV incidents involving White victims when compared with other racial/ethnic groups (Dichter et al, 2011; Eitle, 2005; Hamilton & Worthen, 2011; McCormack & Hirschel, 2018).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%
“…Rape by an intimate partner is one of the most under-reported and unsubstantiated crimes. 230 Many women, of all ages, do not perceive coerced sex in intimate relationships as rape because of the intimate nature of the relationships. 231 Some feel that they are obliged by their marital status to submit to their husband's sexual wishes.…”
Section: Victims Of Intimate Rape: the Case Of Sexual Abuse By An Intmentioning
confidence: 99%
“…In the absence of risk assessment tools, police officers used their subjective judgment and experience to assess risk. Police officers most commonly respond to incidents of IPV without a risk assessment tool, instead taking into consideration the characteristics of the incident (Tatum & Pence, 2015;Dawson & Hotton, 2014;Poon et al, 2014;Durfee & Fetzer, 2016;Kane, 1999). These characteristics tend to include situational, offender, and victim factors.…”
Section: Introductionmentioning
confidence: 99%
“…Male police officers who score high in sexism show a preference for conditional law enforcement in cases of IPV (Gracia et al, 2014). Further to this point, many officers do not view sexual abuse as a form of IPV, which results in a decision not to respond to these calls with as much frequency (Durfee & Fetzer, 2016;Johnson et al, 1994). While this is troubling, progressive policing philosophy and the gender of the officer have been found to increase enlightened views of IPV and impact responses in a positive way (DeJong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%